Establishment of feline embryonic stem cells from the inner cell mass of blastocysts produced in vitro - Takumi Yoshida; Masaya Tsukamoto; Kazuto Kimura; Miyuu Tanaka; Mitsuru Kuwamura; Shingo Hatoya (Regenerative Therapy)
Introduction: The rising number of cats as pets and the growing interest in animal welfare have led to an increased need for the latest treatments in feline veterinary medicine. Among these, veterinary regenerative medicine using pluripotent stem cells is gaining significant attention. However, there have been no reports on establishing feline embryonic stem cell (ESC) lines that possess the pluripotent potential and the ability to differentiate into three germ layers. Methods: In this study, we isolated three inner cell masses from feline in vitro-derived blastocysts and subcultured them in a chemically defined medium (StemFit AK02N). We assessed the expression of undifferentiated markers, the ability to differentiate into the three germ layers, and the karyotype structure. Results: We established three feline ESC lines. Feline ESCs exhibited positive staining for alkaline phosphatase. RT-qPCR analysis revealed that these cells express undifferentiated marker genes in vitro. Immunostaining and flow cytometry analysis demonstrated that feline ESCs express undifferentiated marker proteins in vitro. In the KSR/FBS medium with or without Activin A, feline ESCs differentiated into all three germ layers (ectoderm, endoderm, and mesoderm), expressing specific marker genes and proteins for each germ layer, as evidenced by RT-qPCR, immunostaining, and flow cytometry. Furthermore, we confirmed that feline ESCs formed teratomas comprising all three germ layers in mouse testes, demonstrating de novo pluripotency in vivo. We also verified that the feline ESCs maintained a normal karyotype. Conclusions: We successfully established three feline ESC lines, each possessing pluripotent potential and capable of differentiating into all three germ layers, derived from the inner cell masses of blastocysts produced in vitro.